Implementasi Pembelajaran Model Inquiry Berbantuan Android Terhadap Kemampuan Berpikir Kritis dan Sikap Ilmiah Siswa Pada Konsep Klasifikasi - Eli Herliyawati; Anna Fitri Hindriana; Sofyan Hasanudin Nur (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
This study  aimed  to improve the critical thinking ability and scientific attitude of junior high school students’ using implementation of inquiry learning with android at plant classification.This research method use quasy experiment with research design pre-test post-test control group design. The Population in this study were all seventh grade students of SMP Negeri 1 Garawangi 2019/2020 academic years. The sample in the research using the purporsive samples. The experiment class was treated using an inquiry learning with android model consisting of 29 students and the control class was treated with conventional method consisting of 28 students’. Data collection use a description test for critical thinking skills, a scientific attitude rubic for scientific attitudes and a questionnaire for student responses. Research hypothesis testing uses paired two-sample T-test with the help of SPSS 17 software. The results of the research showed that: (1) the implementation of learning inquiry model with android is well implemented, marked by an average percentage of 100 % with a very upward category. (2) There is an increased in students’ critical thinking ability with moderate N-gain criteria (0,55) and the calculated value of 10,136 at the sig level 0,05. (3) Scientific attitudes get an average total value (80) including both categories. (4) There is a corretation between students’ critical thinking ability with students’ scientific attitudes with a probability coefficient of 0,001 0,025 and a pearson correlation value of 0,442**.(5)  The majority of student (88%) gave positive responses to the application of the inquiry model with android. Thus, students’ critical thinking ability and scientific attitudes increase through the model inquiry with android